Civilidad a la mexicana. Lecturas de la Historia Antigua de México de Francisco Clavijero en la prensa virreinal de Buenos Aires (1801) - Maggio-Ramírez, Matías (El Colegio de México, 2018)
The Storia antica del Messico by Francisco Javier Clavijero circulated in its Italian edition in the main cities of America in the late eighteenth and early nineteenth centuries. The diffusion and appropriation of its ideas are reflected in the Telégrafo Mercantil, Rural, Político, Económico e Historiográfico del Río de la Plata. In spite of the problems that made it difficult for the work of Clavijero to be published in Spanish, a local translation was published in Buenos Aires. The work was read as a vindication of America within the framework of the ideas of the Enlightenment about civilized society that the Creole elite fomented in the press.